The Strengths Use Scale: Psychometric Properties, Longitudinal Invariance and Criterion Validity - van Zyl, Llewellyn E.; Arijs, Diane; Cole, Matthew L.; Gliíska-Newes, Aldona; Roll, Lara C.; Rothmann, Sebastiaan; Shankland, Rebecca; Stavros, Jacqueline M.; Verger, Nicolas B. (Frontiers in Psychology, 2021)
Strengths use is an essential personal resource to consider when designing higher-educational programs and interventions. Strengths use is associated with positive outcomes for both the student (e.g., study engagement) and the university (e.g., academic throughput/performance). The Strengths Use Scale (SUS) has become a popular psychometric instrument to measure strengths use in educational settings, yet its use has been subjected to limited psychometric scrutiny outside of the U.S. Further, its longitudinal stability has not yet been established. Given the wide use of this instrument, the goals of this study were to investigate (a) longitudinal factorial validity and the internal consistency of the scale, (b) its equivalence over time, and (c) criterion validity through its relationship with study engagement over time. Data were gathered at two-time points, 3 months apart, from a sample of students in the Netherlands (n = 360). Longitudinal confirmatory factor analyses showed support for a two-factor model for overall strengths use, comprised of Affinity for Strengths and Strengths Use Behaviors. The SUS demonstrated high levels of internal consistency at both the lower- and upper bound limits at both time points. Further, strict longitudinal measurement invariance was established, which confirmed the instrument's temporal stability. Finally, criterion validity was established through relating strengths use to study engagement at different time stamps. These findings support the use of the SUS in practice to measure strengths use and to track the effectiveness of strengths use interventions within the higher education sector.